2023
DOI: 10.55908/sdgs.v11i7.625
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Forecasting of Production an Agricultural Product

Vahid Amrahov Tofiq,
Narmin Mirzazadeh Gabil,
Murad Taghiyev Zahid
et al.

Abstract: Purpose: The purpose of the research is to analyze the dynamics of agricultural production, to determine the effect of different parameters on the result of production with the help of an econometric model, and to enforce production forecasting.   Methods: The data of the Statistical Committee of the Azerbaijan Republic for the last 15 years were used in the research. According to the obtained data, using the EXSEL software package, the dependence between the production of agricultural products and affecting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The growth and survival of South Africa's sugar industry will depend largely on its ability to compete with rivals in this market in addition to increasing local production. Tofiq et al, (2023) indicated that increasing production is currently maintaining its relevance both in terms of meeting the necessary raw material needs of the country as well as solving the food problem and eliminating dependence on imports. The country's competitive ability is crucial for long-term survival in the home sugar industry.…”
Section: Introductionmentioning
confidence: 99%
“…The growth and survival of South Africa's sugar industry will depend largely on its ability to compete with rivals in this market in addition to increasing local production. Tofiq et al, (2023) indicated that increasing production is currently maintaining its relevance both in terms of meeting the necessary raw material needs of the country as well as solving the food problem and eliminating dependence on imports. The country's competitive ability is crucial for long-term survival in the home sugar industry.…”
Section: Introductionmentioning
confidence: 99%